Alignment of Poetry Instructional Design with Cognitive Load Theory Principles: A Survey of Junior High School Teachers - Rudi Adi Nugroho; Indra Nugrahayu Taufik; Yulia Puspita; Encep Kusumah; Eki Nugraha; Nurulrabihah Mat Noh (UIN Raden Mas Said Surakarta, Indonesia, 2026)
This study intends to analyze the use of presentation-based poetry teaching material design based on the concepts of Cognitive Load Theory (CLT) for Indonesian language instructors in junior high schools in Bandung and Cimahi. In teaching poetry as a complicated literary text, the cognitive load must be carefully managed so that the process of comprehension does not surpass the capacity of students. The research was conducted by using a survey, descriptive-evaluative approach, involving 69 Indonesian language teachers at junior high schools in Bandung and Cimahi. The tools were built in accordance with the three dimensions of CLT: management of intrinsic load, reduction of extraneous load, and optimization of germane load. The data were analyzed descriptively to show the patterns of instructional material design and their conformance to CLT principles. The study found that the use of PowerPoint and Canva is very much present in poetry learning. However, the design still does not entirely comply with the principles of CLT. The presenting materials in the learning process are not yet fully organized considering the effectiveness of material distribution. High text density and non-instructional graphic elements can lead to an increase in unnecessary load. Some of the presentation materials include reflection tasks that might help alleviate cognitive load. The results suggest that the instructional design quality of the poetry teaching materials is not fully consistent with the concepts of Cognitive Load Theory (CLT). The present instructional materials, although not entirely consistent with the principles of CLT, offer significant potential for further growth by including media based on digital technology. Studi ini bertujuan untuk meneliti penerapan desain bahan ajar puisi berbasis presentasi berdasarkan prinsip-prinsip Teori Beban Kognitif (CLT) bagi guru bahasa Indonesia di sekolah menengah pertama di Kota Bandung dan Kota Cimahi. Pengajaran puisi sebagai teks sastra yang kompleks perlu melibatkan pengelolaan beban kognitif secara hati-hati agar proses pemahaman tidak melebihi kemampuan siswa. Studi ini adalah penelitian survei dengan metodologi deskriptif-evaluatif, yang dilakukan pada 69 guru bahasa Indonesia di sekolah menengah pertama di kota Bandung dan Cimahi. Alat-alat tersebut dirancang berdasarkan tiga dimensi CLT, yaitu manajemen beban intrinsik, pengurangan beban ekstrinsik, dan optimalisasi beban germane. Data dievaluasi secara deskriptif untuk mengungkap pola desain bahan ajar dan kesesuaiannya dengan prinsip-prinsip CLT. Temuan studi menunjukkan bahwa penggunaan Powerpoint dan Canva cukup menonjol dalam pembelajaran puisi. Akan tetapi desainnya masih belum sepenuhnya sesuai dengan prinsip-prinsip CLT. Bahan presentasi materi dalam pembelajaran belum sepenuhnya disusun secara baik dengan mempertimbangkan efektivitas penyampaian materi. Terdapat banyak kepadatan teks dan fitur grafis non-instruksional yang dapat menyebabkan peningkatan beban berlebih. Pada beberapa bahan presentasi terdapat kegiatan reflektif dapat mengurangi beban kognitif. Hasil ini menunjukkan bahwa kualitas desain instruksional bahan ajar puisi belum sepenuhnya sesuai dengan prinsip Cognitive Load Theory (CLT). Meski belum sepenuhnya sesuai dengan prinsip CLT, bahan ajar yang ada memiliki potensi yang besar untuk dikembangkan lagi dengan melibatkan media-media berbasis teknologi digital.